The Myth of Inevitable US Defeat in Vietnam, 1st Edition - Walton, Dale (Routledge, 2020)
This book offers a dispassionate strategic examination of the Vietnam conflict that challenges the conventional wisdom that South Vietnam could not survive as an independent non-communist entity over the long term regardless of how the United States conducted its military- political effort in Indochina.